Effects of Pubertal Maturation on ACL Forces During a Landing Task in Females. Issue 12 (October 2021) - Nasseri, Azadeh; Lloyd, David G.; Minahan, Clare; Sayer, Timothy A.; Paterson, Kade; Vertullo, Christopher J.; Bryant, Adam L.; Saxby, David J.
Background: Rates of anterior cruciate ligament (ACL) rupture in young people have increased by >70% over the past two decades. Adolescent and young adult females are at higher risk of ACL injury as compared with their prepubertal counterparts. Purpose: To determine ACL loading during a standardized drop-land-lateral jump in females at different stages of pubertal maturation. Study Design: Controlled laboratory study. Methods: On the basis of the Tanner classification system, 19 pre-, 19 early-/mid-, and 24 late-/postpubertal females performed a standardized drop-land-lateral jump while 3-dimensional body motion, ground-reaction forces, and surface electromyography data were acquired. These data were used to model external biomechanics, lower limb muscle forces, and knee contact forces, which were subsequently used in a validated computational model to estimate ACL loading. Statistical parametric mapping analysis of variance was used to compare ACL force and its causal contributors among the 3 pubertal maturation groups during stance phase of the task. Results: When compared with pre- and early-/midpubertal females, late-/postpubertal females had significantly higher ACL force with mean differences of 471 and 356 N during the first 30% and 48% to 85% of stance, and 343 and 274 N during the first 24% and 59% to 81% of stance, respectively, which overlapped peaks in ACL force. At the point of peak ACL force, contributions from sagittal and transverse plane loading mechanisms to ACL force were higher in late-/postpubertal compared with pre- and early-/midpubertal groups (medium effect sizes from 0.44 to 0.77). No differences were found between pre- and early-/midpubertal groups in ACL force or its contributors. Conclusion: The highest ACL forces were observed in late-/postpubertal females, consistent with recently reported rises of ACL injury rates in females aged 15 to 19 years. It is important to quantify ACL force and its contributors during dynamic tasks to advance our understanding of the loading mechanism and thereby provide guidance to injury prevention. Clinical Relevance: Growth of ACL volume plateaus around 10 years of age, before pubertal maturation, meaning that a late-/postpubertal female could have an ACL of similar size to their less mature counterparts. However, late-/postpubertal females have higher body mass requiring higher muscle forces to accelerate the body during dynamic tasks, which may increase ACL loading. Thus, if greater forces develop in these females, in part because of their increased body mass, these higher forces will be applied to an ACL that is not proportionally larger. This may partially explain the higher rates of ACL injury in late-/postpubertal females.